Peranan Petani Wanita dalam Meningkatkan Perekonomian Keluarga di Desa Sakra Selatan - Muhamad Zaril Gapari (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
The purpose of this study is to know the role of women in improving family economy in the South Sakra Village, Sakra District East Lombok Year. The type of research used in this study is research Qualitative descriptive. The data collection technique used is technique observation, documentation, and interviews. The results of the study indicate that there are several factors within socio-cultural life of the people of the Sakra Village south of Dasan Tereng Village which affects the women farmers to help in life the family economy, namely: mutual cooperation and help in the life of the farmer's family. and there are four important factors that become encouraging women of South Sakra Village farmers to take part in help the family's economic life, including: (1) environmental factors the availability of supporting facilities in the form of agricultural land and markets that can support in expanding marketing of agricultural products (2) economic factors, namely: the decreasing level of income of farmers, in the farming community Southern sakra village has three forms of the role of female farmers in life his family, namely: in family income, in financial management and in household settings. (3) family factors, namely: number dependents, the more the number of dependents the more you have to fulfilled. (4) education factor, which does not require higher education, so this work becomes an alternative. The form of the role of female farmers in improving the family economy in the South Hamlet Sakra Village Dasan Tereng has three things: (1) working in the agricultural sector, (2) working in the livestock sector, (3) working in the trade sector. Based on the things above women farmers in the southern sakra village have a dual role, namely public role and domestic role to help economic life his family.